The influence of bank loan officers attitudes on funding decisions : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Duff, Shirley Moana (Massey University, 1998)
A conflicting body of evidence surrounds womens claims that they are discriminated against when it comes to obtaining business loans. Fay and Williams (1991) found that when identical loan applications were submitted by men and women, women were less likely to be granted a loan. It was proposed in this study that gender discrimination could be occurring as a result of bank loan officers attitudes about women as successful business owners. Seventy bank loan officers from North Island branches of the ANZ, ASB and WestpacTrust banks filled in questionnaires assessing their attitudes towards women, men and successful business owners (Buttner & Rosen, 1988). Bank loan officers also read a mock loan application (Fay & Williams, 1991) and indicated whether they would grant the loan. Results showed that bank loan officers did not differentially approve bank loans on the basis of the applicants gender (male or female) or level of education (Highschool or University). Loan approval was harder for male applicants to obtain as 'type of business entering' and 'lease agreement' were considered more important for males than females. Attitudes of bank loan officers indicated that they perceived women, compared to men, to be least like successful business owners. These results were discussed in relation to bank loan officers and prospective business owners. Limitations of the study included the possibility of response bias, participants being aware of the purpose of the study and the fact that the loan application was limited to one scenario and within the context of a hypothetical situation. Suggestions for future research include investigating other sources of funding for small business owners and the occurrence and effect of occupational sex-typing.
Keywords: New Zealand; Bank employees; Attitudes; Bank loans; Decision making; Discrimination in consumer credit; Businesswomen